Avaliação clinicopatológica e imuno-histoquímica de tumores odontogênicos queratocísticos associados à Síndrome de Gorlin (Síndrome do carcinoma nevóide basocelular) Estudo colaborativo internacional. - Delgado, Renata Zoraida Rizental (2015)
Introduction: Gorlin syndrome (GS) also known as Nevoid Basal Cell Carcinoma Syndrome, is a rare disease resulting from mutations in Patched-1 gene and characterized by triad of disorders comprising multiple basal cell carcinomas, numerous keratocystic odontogenic tumors (KOT) and skeletal abnormalities. About 90% of patients develop KOTs in gnathic bones, preferably in the posterior mandible, presenting radiographically as radiolucent lesions uni- or multilocular. Studies suggests that KOTs associated with GS (KOTGSs) have distinct and more aggressive behavior compared to those who developing sporadically (KOTSPs). Objectives: This study aimed at comparing clinical, histopathological and immunohistochemical features of KOTSPs and KOTGSs from different institutions in Brazil and abroad, and understand the role of proteins associated with proliferation/cell cycle (p53, p63 and Ki-67), the alpha-smooth muscle actin (α-SMA) and syndecan-1 (CD138) in an attempt to associate the expression with biological behavior of KOTs. Methodology: Were previously reviewed and selected 30 KOTGSs and 8 KOTSPs, in which were performed qualitative and semi-quantitative analysis histopathological and immunohistochemical to p53, p63, Ki-67, SMA and CD138. Results: 30 cases of KOTGSs were obtained from 12 patients with GS, 5 females (41.66%) and 7 men (58.33%); whereas in group of KOTSPs, 5 cases (62.50%) was in females and 3 males (37.50%). About 58.33% of patients with GS had more than one lesion throughout life. The average age of individuals with GS was 14.66 ± 16.81 years, while in patients with KOTSPs was 41 ± 39.59. The predominant radiographic pattern was radiolucent unilocular, preferably affecting the posterior mandible. Histopathological features in both groups was analyzed, and the most frequent was pleomorphism in KOTGSs. In addition, there was increased expression of p53 and p63 in KOTGSs and similar expression of SMA and Ki-67 between groups. It was also observed that there was a lower reactivity for CD138 in the basal epithelial layer of KOTGSs and stromal expression of CD138 was similar between the groups. Conclusions: Agressiveness of KOTGSs can be explained by increased cellular pleomorphism rate and expression of p53 and p63 and tendency to loss of syndecan-1 expression compared to KOTSPs.